Strength calculation for fiber concrete slabs under high velocity impact - Ustinov A. Artem; Kopanitsa D. G. Dmitry Georgeevich; Belov N. Nikolay; Jugov N. Nikolay; Jugov A. Alexey; Koshko B. Bogdan; Kopanitsa G. D. Georgy Dmitrievich (2017, 2017)
Title screen